Y autosome translocation and complex chromosome rearrangement in cri du chat syndrome. Issue 2 (April 1978) - Mattei, J F; Mattei, M G; Coignet, J; Giraud, F
Abstract : An unbalanced Y autosome translocation t(5;Y) and an apparently balanced translocation t(2;13) are identified with the Q and R banding in a 7-year-old boy with severe encephalopathy and a multiple malformation syndrome. At birth, the clinical diagnosis of 'cri du chat' syndrome based on the characteristic crying was not confirmed after karyotyping, using conventional staining techniques.